Sensitive and selective quantification of free and total malondialdehyde in plasma using UHPLC-HRMS - Mendonça, Rute; Gning, Ophélie; Di Cesare, Claudia; Lachat, Laurence; Bennett, Nigel C; Helfenstein, Fabrice; Glauser, Gaëtan (My University, 2017)
Quantification of malondialdehyde (MDA) as a marker of lipid peroxidation is relevant for many research fields. We describe a new sensitive and selective method to measure free and total plasmatic MDA, using derivatization with 2,4-dinitrophenylhydrazine (DNPH) and ultrahigh performance liquid chromatography-high resolution mass spectrometry (UHPLC-HRMS). Free and total MDA were extracted from minute sample amounts (10 μL) using acidic precipitation and alkaline hydrolysis followed by acidic precipitation, respectively. Derivatization was completed within 10 min at room temperature, and the excess DNPH discarded by liquid-liquid extraction. Quantification was achieved by internal standardization using dideuterated MDA as internal standard. The method lowest limit of quantification (LLOQ) was 100 nM and linearity spanned > 3 orders of magnitude. Intra- and inter-day precisions for total MDA were 2.9% and 3.0%, respectively, and those for free MDA were 12.8% and 24.9%, respectively. Accuracy was 101% and 107% at low and high concentrations, respectively. In human plasma, free MDA levels were 120 nM (SD 36.26) and total MDA levels were 6.7 μM (SD 0.46). In addition, we show the applicability of this method to measure MDA plasma levels from a variety of animal species, making it invaluable to scientists in various fields.
Keywords: Fatty acids; Oxidation; Lipid peroxidation; Malondialdehyde